Role of fucosyltransferases in the association between apomucin and Lewis antigen expression in normal and malignant gastric epithelium. Issue 3 (1st September 2000) - López-Ferrer, A; de Bolós, C; Barranco, C; Garrido, M; Isern, J; Carlstedt, I; Reis, C A; Torrado, J; Real, F X
Abstract : BACKGROUND: In normal gastric epithelium, MUC5AC is detected in superficial epithelium associated with Lewis type 1 antigens and MUC6 is detected in antral glands with Lewis type 2. Therefore, the stomach constitutes an excellent model to examine the role of glycosyltransferases in determining the specificity of apomucin glycosylation. AIMS: To determine the molecular basis of this association and to examine changes in expression of gastric and intestinal apomucins and their association with Lewis antigens during the gastric carcinogenesis process. METHODS: Fucosyltransferase (FUT1, FUT2, FUT3) and mucin (MUC5AC, MUC6) transcripts were detected using reverse transcription-polymerase chain reaction. Apomucin (MUC2, MUC4, MUC5AC, MUC6) and Lewis antigen (types 1 and 2) expression were analysed using single and double immunohistochemistry and in situ hybridisation. RESULTS: In the normal stomach, FUT1 is exclusively detected associated with MUC6; FUT2 is only detected when MUC5AC is present. This co-regulation is lost in gastric tumours, as is differential expression of MUC5AC and MUC6 in normal gastric epithelial cells. In gastric tumours, especially those with the intestinal phenotype, MUC2 and MUC4 genes are upregulated, and gastric-type and intestinal-type mucins are coexpressed. These changes are early events in the gastric carcinogenesis process, as they are detected in intestinal metaplasia. CONCLUSIONS: The glycosylation pattern found in normal gastric epithelium is dictated by the specific set of fucosyltranferases expressed by the cells rather than by the apomucin sequence. The development of intestinal metaplasia and gastric cancer is associated with the appearance of cellular phenotypes that are absent from normal epithelium.